An Adaptive Contrast Enhancement Algorithm with Details Preserving - Jing Rui Tang; Nor Ashidi Mat Isa (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This paper presents an adaptive contrastenhancement algorithm with details preserving (ACEDP) toenhance gray-scale image. Initially, the input image is classifiedinto low-, middle- or high-level image based on the gray-leveldistribution of maximum number of pixels. The proposedACEDP algorithm assigns different plateau functions fordifferent type of image and histogram clipping is then performedfollowed by histogram equalization. Simulation results show thatthe proposed technique outperforms several techniques inliterature. It demonstrates good ability in contrast enhancementas well as details preservation.